The current perspective of oxygen therapy and ventilatory support in acute heart failure - Waranugraha, Yoga (Universitas Brawijaya, 2025)
Oxygen (O2) therapy in acute heart failure (AHF) is purposed to address hypoxemia and thereby avert irreversible harm to essential organs caused by cellular hypoxemia. The O2 therapy is recommended for patients with AHF who have an oxygen saturation (SpO2) level below 90% or an oxygen partial pressure (PaO2) below 60 mmHg. The initial strategy of O2 therapy in AHF involves administering O2 using the nasal, face mask, or non-rebreathing mask (NRBM). In more severe clinical conditions or respiratory distress, non-invasive positive pressure ventilation (NIPPV) or intubation with mechanical ventilation may needed.